PENGGUNAAN AYAT ALQURAN DALAM PENGOBATAN ALTERNATIF (STUDI LIVING QURAN PADA PRAKTIK PENGOBATAN ALTERNATIF PATAH TULANG USTADZ SANWANI DI DESA MEKAR KONDANG – TANGERANG) - Irawan, Ferdiansyah (Jurnal Ilmiah Pendidikan dan Keislaman, 2021)
Alquran is kalamullah that can be used to cure all diseases, using Alquranas a medicine is a matter that has been determined by the teachings, and not only that, the phenomenon that occur in society also help to ensure the efficacy of Alquran. How many of us get those who are sick, who do not get healed but, thanks to the grace and forgiveness of Allah who always surrounds them, namely through reading the holy verses of the Quran, their disease can be cured with the blessings of the Quran. This writing reveals the study of the living Quran in the use of the verses of the Quran in alternative medicine and their effects